132 Newbury Street, 1927 - Unknown (Tufts Archival Research Center, 2005)
Street-level view south-southeast of 132 Newbury Street, located between Clarendon Street to the east-northeast and Dartmouth Street to the west-southwest. The facade of the house faces north-northwest towards Newbury Street. 4 1/8 x 2 3/8, 4 3/8 x 2 5/8 overall Photographs